Qiro'ah Method in TPQ Development Programin Tomori Village, Bacan Kec, South Halmahera Regency - Muhammad Wardah; Irfan Irfan; Ujaifah Aden (Syntax Idea)
This study discusses how to apply the "Qiro'ah Method in the Al-Qur'an Education Park Development Program (TPQ) in Tomori Village, Bacan District, South Halmahera Regency". The purpose of this study was to obtain information about the benefits of applying the Qiro'ah method and developing skills in reading the Koran. In addition, it also reveals the advantages of the Qiro'ah method. This study uses a qualitative descriptive approach, while the subjects of the research are teachers, parents and students. Sources of data used are primary data and secondary data. Data were obtained using observation, interview and documentation techniques. Data were analyzed using reduction techniques, data displays, and conclusion draws. The results showed that the application of the Qiro'ah method in Tomori Village, Bacan District, South Halmahera Regency, not all TPQ used the Qiro'ah method, but there was one TPA that had started using the method. In general, for material that is more difficult, the teacher will explain while writing examples on the blackboard. In teaching the Qiro'ah method, the teacher applies a private system, namely by listening to students one by one or individually, and the Qiro'ah method is arranged in a systematic and interesting way so that it can help students. quickly learn to read the Koran. The development of students' reading skills is carried out by learning tajwid science more specifically, memorizing short surahs and when they deposit the students' memorization will immediately correct their tajwid reading. Very important for developing students' reading skills is how often students read the Koran at home.